Expression of EGFR in Pituitary Corticotroph Adenomas and Its Relationship With Tumor Behavior - Liu, Xiaohai; Feng, Ming; Dai, Congxin; Bao, Xinjie; Deng, Kan; Yao, Yong; Wang, Renzhi (Frontiers in Endocrinology, 2019)
Objective: Epidermal growth factor receptor (EGFR) has been found to localize in several human neoplasms and has been shown to have a significant correlation with adenomaigenesis and patient prognosis. EGFR is also overexpressed in pituitary corticotroph adenomas. However, its clinical significance and relationship with tumor behavior, especially tumor recurrence status, remain obscure. The purpose of the present study was to identify the expression patterns of EGFR and its downstream signaling pathway molecules in pituitary corticotroph adenomas and to investigate the association of EGFR with clinicopathological characteristics and tumor recurrence. Methods: Fifty-two sporadic pituitary adenoma specimens and six normal pituitary glands were collected. The expression levels of EGFR and its downstream signaling molecules in each sample were evaluated and quantified using immunohistochemistry and Western blot. The relationships of EGFR expression with clinicopathological characteristics and tumor recurrence status were analyzed. Results: EGFR was overexpressed in 55.8% of the pituitary corticotroph adenomas and in 1 of 6 of the normal adenohypophysial tissues. The expression degree was significantly higher in pituitary corticotroph adenomas than in normal adenohypophysial tissues. In EGFR-overexpressing adenomas, the downstream pathway phosphorylated Erk (p-Erk) was also significantly activated. Moreover, the expression levels of EGFR were positively correlated with the adrenocorticotropic hormone (ACTH) and cortisol levels but were not correlated with age, sex or symptom duration. The expression levels of EGFR, phosphorylated EGFR (p-EGFR) and p-Erk were significantly up-regulated in the recurrent adenoma group compared with those in the non-recurrent adenoma group (all p < 0.05). The expression levels of EGFR were strongly correlated with the recurrence-free interval (p = 0.005, CC = −0.31). Conclusion: The expression levels of EGFR and its downstream pathway components were significantly increased in pituitary corticotroph adenomas compared to the levels in normal adenohypophysial tissues. EGFR expression levels were positively associated with the ACTH and cortisol levels and with tumor recurrence status. Pituitary corticotroph adenomas with high EGFR expression levels were correlated with an increased recurrence rate and a decreased recurrence-free interval. EGFR could be used as a promising biomarker for predicting pituitary corticotroph tumor recurrence.